The Impact of Public Sector Employee Performance on Citizen Satisfaction: The Case of MEHE - Berro, Zahraa (Technium Social Sciences Journal, 2021)
Governments nowadays are being more attentive to the importance of gaining citizens’ satisfaction and trust, knowing that their trust would maintain political stability, allowing them to have more control and function easily and more effectively. One of the influencers of citizens’ satisfaction is the public sector services and the performance of the employees in this sector. This research studies the micro performance theory by studying the relation between the performance of the ministry of education and higher education in Lebanon and citizen satisfaction. To study this relation a survey was conducted to study the level of citizen satisfaction toward the ministry’s performance. The survey also assessed the performance of the Ministry of Education and Higher Education employees from the citizens’ perspective. Our research also compared the public and private university graduates’ satisfaction towards the ministry’s performance since the survey was distributed online to graduated students among the Lebanese public university and graduates from different Lebanese private universities. The result of the survey along with existing data was analyzed to study the impact of the ministry’s performance towards citizen satisfaction leading to a conclusion regarding the effect on the level of citizen’s trust towards government institutes.